Plant Decorations on Pottery in the Half Culture Period in Syria (Damascus University Journal of arts and humanities sciences, 2021)
This research is concerned with the study of plant decorations that were part of the main scene on some pottery vessels in the Chalcolithic period in Syria. The research is concerned with studying the representation of these plants by allied artists during the Halaf culture period, discussing the patterns in which they appeared and the place of their appearance and whether they were singularly or in conjunction with other formations (animals and birds or geometric shapes), and trying to interpret their symbols and their connotations, in order to answer several questions, including : Did the oaths use plant decoration on pottery for its connotations and meaning, or only admired its shape and aesthetics؟
Keywords: Plant Decorations; Pottery